Studi Kuat Tekan Tanah Pasir Berlempung yang Distabilisasi Menggunakan Abu Gunung Merapi - Setyanto Setyanto; Andius Dasa Putra; Aditya Nugraha (UNIVERSITAS LAMPUNG, 2013)
The tested soil sample in this research is sandy clay soil. The variations of procentage are 5%,10%, 15%, and 20%. Each of samples are cured in 14 days. Based on the physical soil propertiesinvestigation, AASHTO classified the soil sample into A-2-6 group (sandy clay soil), while USCSclassified the soil sample as soil with rough granules into SC group.The results of the research in the laboratory showed that the additive material using Merapi vol -canic ash could improve the physical and mechanical properties of organic clay soil. In the physi-cal test such as unit weight and Atterberg limit tests, the values decreased after it, while the me-chanical test of Merapi ash sample showed it could improve the value of unconfined compressionstrength soil. Based on the result of unconfined compression stregth test, soil which is stabilizedusing the ash of Mount Merapi increase until the optimum ash content about 20%.